Genetics of Behçet's Disease: Functional Genetic Analysis and Estimating Disease Heritability - Ortiz-Fernández, Lourdes; Sawalha, Amr H. (Frontiers in Medicine, 2021)
Behçet’s disease is a chronic multisystemic inflammatory disorder characterized by recurrent oral and genital ulcers. Although its etiology remains unclear, it is thought that both genetic and environmental factors contribute to the onset and progression of Behçet’s disease. Here, we provide an updated view of the genetic landscape and architecture of Behçet’s disease. Large-scale genetic studies performed to date revealed 21 genetic susceptibility loci associated with the disease at a GWAS level of significance (p value= 5 x 10-8). We performed epigenetic pattern enrichment analysis in Behçet’s disease associated loci, providing new insights into the molecular mechanisms underlying its pathophysiology. Our data suggest the crucial involvement of several immune cell types, including natural killer cells, monocytes, and B cells in the pathogenesis of the disease. Pathway enrichment analysis identified important biological processes involved in the disease. Using large-scale genetic data available from ~200 immune-related loci (Immunochip), we estimate Behçet’s disease heritability to be at least 16%. We further used the same approach to estimate the heritability explained by the known Behçet’s disease-associated loci, suggesting that they explain ~ 60% of the genetic component underlying Behçet’s disease. These results indicate a significant role of non-genetic factors in causing Behçet’s disease and that additional genetic variation influencing the risk of Behçet’s disease remains to be identified. Finally, we calculated a cumulative genetic risk score across populations reinforcing the link between geographic variations in disease prevalence with its genetic component.